Social economy landscape in Chile: the gap between formal and substantive definition - Letelier Araya, Eduardo; Vanhulst, Julien; Cid Aguayo, Beatriz; González Meyer, Raúl (REVESCO. Revista de Estudios Cooperativos, 2019)
This article seeks to dimension and characterize the social economy sector in Chile by 2015, adapting the typology proposed by EESC / CIRIEC for Europe. Based on the systematization of primary quantitative data collected for the study, a panoramic vision is proposed that is comparable with other countries using the EESC / CIRIEC typology. In the same way, this vision complements studies carried out on the non-commercial subsector of the social economy in Chile. According to the results obtained in the study, in 2015 the social economy employed 313,591 paid workers in Chile and it generated US 8,963 million of monetary incomes. These figures are equivalent to 3.8 percent of employment and 3.7 percent of Chile’s GDP, respectively, placing the country below the average of the European Union and above countries of comparable per capita income such as Greece or Poland. However, due to the high rate of informal organizations and companies these values could be underestimated in a range of 64 to 83 percent, respectively. Moreover, background information on voluntary or unpaid employment in the non-commercial subsector would point to doubling of the number of workers participating in the social economy sector in Chile. The article concludes with a reflection on the tension between formal and substantive definitions of the social economy and the difficulties of defining unambiguous demarcation criteria, in response to different situations that arose in the process of gathering information for the study.